RESEARCH OF RAILWAY TRANSPORTATION OF FREIGHT BY GROUP AND SINGLE CARS (Transport systems and technologies, 2021)
The influence of the existing conditions of operational work at transportation of cargoes by group and single cars is investigated. An analysis of modern approaches to improving the efficiency of the car fleet and the competitiveness of railway transport in the transport market of Ukraine. The most perspective approaches and directions of improvement of cargo delivery systems are allocated. A study of the efficiency of the organization of transportation by the criterion of total car-hours of downtime under accumulation. A mathematical model of chemical cargo transportation by carriage, group shipments and transportation of container trains with accumulation to technical norms of trains in the directions of transportation has been developed. The efficiency of two models of chemical cargo shipment organization is compared and a more efficient transportation option is identified. It is established that for more efficient use of rolling stock and reduction of car turnover there is transportation of goods in cars as a part of a container train. The influence of the components of the car turnover on its final value is analyzed. A study of the cost of transportation of benzene in tanks and tank containers in some areas. According to research, the cost of transporting benzene in tank containers on railway ownership platforms is twice less than in private tanks and tanks of Ukrzaliznytsia fleet. These recommendations will improve the process of transportation and increase the volume of goods by rail.
Keywords: cargo transportation, transport market, competitiveness, cargo delivery, car turnover.